Appendiceal stricture following Mini-ACE® enema button placement: a case report - Signe Olsbø; Kjetil Næss Ertresvåg; Kristin Bjørnland (Journal of Pediatric Surgery Case Reports)
Introduction: Few studies have looked at complications related to antegrade continence enema (ACE) devices. This report discusses a complication of the Mini-ACE® button and how it was managed. Case presentation: The patient was a 7-year-old boy with a history of constipation and fecal incontinence. He first experienced constipation at the age of 1 year. Hirschsprung disease was ruled out by a rectal biopsy. After a multidisciplinary evaluation, he underwent an appendicostomy procedure with a Mini-ACE® for antegrade enemas. The Mini-ACE® functioned well for 1 year. However, after a routine replacement, increased resistance was noted during water installation. When attempting to replace the device, not even a guidewire could be passed through the appendix. Contrast fluoroscopy identified a 2-cm long appendiceal stricture, located about 3 cm from the cecum. Since a new Mini-ACE® could not be inserted, conservative treatment with oral laxatives was initiated. The patient refused rectal enemas. The patient's constipation and fecal incontinence recurred. Three months later he was taken to the operating room to revise the appendicostomy. Through a laparoscopic approach, the stricture was resected, and the two ends of the appendix were anastomosed. At one year of follow-up, the patient has good symptom control, and the use of the Mini-ACE remains uncomplicated. The stricture was likely caused by the inflation of the Mini-ACE® balloon within the appendix. Conclusion: ACE appendicostomies can develop fibrosis if the button balloon is inflated within the appendix. If the fibrotic segment is not too long, resection and appendiceal anastomosis may be a viable option to preserve the appendicostomy.